Victoriomyces antarcticus gen. nov., sp. nov., a distinct evolutionary lineage of the Cephalothecaceae (Ascomycota) based on sequence-based phylogeny and morphology. Issue 4 (15th February 2019) - Davolos, Domenico; Pietrangeli, Biancamaria; Persiani, Anna Maria; Maggi, Oriana
Abstract : In this study, we propose a new genus, Victoriomyces, with a new species, Victoriomyces antarcticus, isolated from soil samples collected in Victoria Land, Antarctica. To determine its taxonomic status and evolutionary relationships, phylogenetic analysis was performed on DNA sequences from the nuclear 18S rRNA, 28S rRNA and the second largest subunit of RNA polymerase II ( RPB2 ) genes. Victoriomyces antarcticus constitutes one well-supported distinct lineage within the Cephalothecaceae (family incertae sedis in Sordariomycetes ), in which the only recognised asexual morphs belong to the genus Phialemonium and to Acremonium thermophilum. Victoriomyces antarcticus can be clearly distinguished from these taxa by means of DNA sequence analysis and its morphological traits that consist in having a Metarhizium -like asexual morph, dark red-coloured disk-like structures, immature bodies and the production of an intense red pigment in the growth media. Finally, we inferred the divergence time of V. antarcticus and the Cephalothecaceae using Bayesian analysis and secondary calibration. The holotype of V. antarcticus is FBL 165. The ex-type strain has been deposited as MUT 3686 T and CCF 6158 T . An additional strain of the species is FBL 577. The MycoBank number is MB 823713 for the genus and MB 823714 for the species.